THE ACT MODEL (ANALYZE, CONNECT, TRANSFORM) FOR DEVELOPING REFLECTIVE SKILLS IN FUTURE ENGLISH TEACHERS: A THEORETICAL FRAMEWORK GROUNDED IN DEWEY, SCHÖN AND BROOKFIELD - Jonibekova Mehriniso Umarbek qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This research introduces the concept of the ACT model (Analyze, Connect, Transform) as a methodological instrument for developing the reflective skills of future English teachers based on the ideas of John Dewey, Donald Schön, and Stephen Brookfield. The article provides an explanation of the interrelations between three phases of the ACT model and the theories of John Dewey, Donald Schön, and Stephen Brookfield respectively. In accordance with the theory of reflective thinking of John Dewey, its three phases and the attitude of wholeheartedness, open-mindedness, and responsibility, the first phase of the ACT model is presented to assist future teachers in examining classroom problems in an active, persistent, and attentive manner. Reflecting in action, reflecting on action, and knowing in action are introduced to analyze the role of the second stage of the model in helping teachers to formulate tacit knowledge and differentiate between problem setting and solving. The four lenses of Stephen Brookfield (autobiographical lens, lens of students' eyes, lens of colleagues' experience, and theoretical lens), together with assumption analysis proposed by the author, enhance the effectiveness of the CONNECT and TRANSFORM phases.